PERENCANAAN BISNIS PADA USAHA ONLINE KAIRAN ACCESSORIES - Fadhilah, Khairana; Ikhram W., M. Abdi Dzil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Covid-19 pandemic has urged Indonesian businesspeople, especially those engaged in fashion, to develop their business online through e-commerce in order to keep up with recent development and to meet market needs. This research aims to identify the business feasibility of Kairan Accessories by analyzing the company’s internal and external factors, to analyze alternate strategies that can be taken, and to analyze the company’s finance. The data of this research was analyzed using investment and profit analysis, IFE matrix, EFE matrix, IE matrix, and SWOT matrix. The results of the investment analysis show that the company has the NPV of IDR 11.344.600, the PI of 2,32, and the IRR of 33.6%. The results of the profit analysis indicate that the company has the BEP of IDR Rp29.090.909 and the contribution margin of 65.71%. The IFE matrix produces the value of 292, while the EFE matrix produces 279. Based on the IE matrix, the company is in the first quadrant, i.e. the aggressive strategy. Therefore, Kairan Accessories is feasible using a strategy that relies on its internal strength to take any possible opportunities which eventually can lead to sales increase.